PP61 Neighbourhoods and Ethnic Differences in Biological 'Wear and Tear'. (10th September 2013) - Molaodi, O R; Leyland, A H; Ellaway, A; Kearns, A; Harding, S
Abstract : Background: We recently showed that ethnic minorities tend to live in deprived neighbourhoods with a high density of fast food outlets and less green space. We examine whether these neighbourhood characteristics were associated with ethnic differences in biological 'wear and tear'. The hypothesis is that ethnic minorities may experience early physiological deterioration as a result of persistent high level coping with chronic neighbourhood stressors. Methods: Individual level data from the Health Surveys for England (1999 and 2004) were combined with area level data on neighbourhood food and physical activity environments, deprivation and ethnic density. A summary biological risk score, allostatic load – AL, was created from nine biological indicators of elevated risk; serum levels of C-reactive protein, fibrinogen, glycated haemoglobin, total and high-density lipoprotein cholesterol, BMI, waist, and systolic and diastolic blood pressure. Multi-level models examined ethnic differences in AL, as a continuous (0–9) and dichotomous (> = 4) score, in relation to neighbourhood and individual level characteristics. Discussion: Black Caribbeans, Pakistani and Bangladeshis had a higher probability of a mean and high risk AL score than Whites, increasing with age, and more clearly delineated among women than men. Individual and area deprivation were related to AL but did not explain ethnic differences in AL. The density of fast food outlets, supermarkets, physical activity facilities, or ethnic density was not associated with AL. Conclusion: Living in deprived neighbourhoods was associated with greater biological wear and tear, independent of individual socio-economic circumstances, but did not explain the worse physiological profiles of some ethnic groups.